STUDI PERBAIKAN (REPAIR) PADA BANGUNAN GEDUNG FAKULTAS SAINS DAN TEKNOLOGI - -, Marwati (Fakultas Sains dan Teknologi UIN ALauddin, 2013)
The development of the use of the building of the Faculty of Science & Technology has increase in students, faculty and staff of the environment. Increased building user switha high frequency impact damage have been seen in some parts of the building. The existence of such defects as early as possible will require an analysis of building defects that would affectless than the maximum functionality on the performance of the building. If damage occurs early and do not get immediate attention and repair searly, it will cause further difficulties in handling. Study sites are in the laboratory building repair science & technology faculty. Descriptive analysis of the examination of damage that occurs in the components/ elements of the main building and the cause than try to find the appropriate repair system. Based on the study based on the standard of maintenances concluded that there is heavy damage on the ceiling and the lighten the plumbing, walls, columns and floors. System repair needs to be done on the ceiling and light repair on the part of besides ceiling. Repair epoxy injection method in mild and moderate damage, severe damage repacked concrete. The need for attention to some of the conditions of the building that has been damaged from the building by doing a real improvement in the not too long. This if left unchecked will affect other parts of the building are around.Keywords: building, repair, maintenance.